Vasculogenic mimicry score identifies the prognosis and immune landscape of lung adenocarcinoma - Yang, Weichang; Li, Zhouhua; Wang, Wenjun; Wu, Juan; Li, Jinbo; Huang, Xiaotian; Zhang, Xinyi; Ye, Xiaoqun (Frontiers in Genetics, 2023)
Background: Lung cancer has a high incidence and mortality rate worldwide. Vasculogenic mimicry (VM) is a specific modality of tumor angiogenesis that could potentially be a new target for tumor therapy. The purpose of this study was to explore the role of VM-related genes in assessing the prognosis and immune landscape of lung cancer. Methods: VM-related genes were obtained from previous studies, and the expression data and clinical data of lung adenocarcinoma (LUAD) patients were obtained from the TCGA database and GEO database. We performed enrichment analysis of 24 VM-related genes and screened hub genes by constructing a protein–protein interaction network and using Cytoscape software. Subsequently, we developed the VM score based on univariate Cox regression analysis and Lasso analysis and validated the VM score on the GSE72094 dataset. In addition, we constructed a nomogram based on the VM score in the TCGA cohort. Finally, we explored the correlation between the VM score and the tumor microenvironment, immune cell infiltration, immune checkpoints, and drug sensitivity. Results: Enrichment analysis revealed that VM-related genes were associated with the HIF signaling pathway and angiogenic pathway. We developed a VM score based on 3 genes (EPHA2, LAMC2 and LOXL2) in LUAD patients. Kaplan-Meier analysis showed that the VM score was associated with poor prognosis in LUAD patients. The receiver operating characteristic curve suggested that the VM score and nomogram are valid predictors for the overall survival of LUAD patients. The VM score was significantly correlated with immune cell infiltration, such as naïve B cells, neutrophils, and eosinophils, and there was a difference in the TME between the high VM score group and the low VM score group. LUAD patients in the high VM score group were more sensitive to antitumor drugs. Conclusion: In summary, the VM score developed in this study is a valuable indicator for evaluating the prognosis and immune landscape of LUAD patients. VM may be a potential target for antitumor therapy in lung cancer.